The Role of Infrastructure Policies in Alleviating Poverty in Indonesia - Nuzul Husnah; Wily Arafah; Budi Santosa; Maria R. Nindita Radyati (International Journal of Social Service and Research (IJSSR), 2023)
Poverty is a complex and multidimensional problem. Therefore, all poverty alleviation efforts must be carried out in a comprehensive manner and various aspects of people's lives. The purpose of this study was to analyze the influence of Infrastructure on economy and poverty, and to analyze government policies to find infrastructure government initiatives for poverty alleviation in Indonesia towards Sustainable Development. A mixed research method was adopted, by combining quantitative and qualitative research, with a sequential explanatory design, used a hypothesis testing method which explains the effect of the independent variable (Infrastructure), on the dependent variable (Poverty Alleviation), with Economic performance as a mediating variable, and Government Policy as a moderating variable, then a qualitative approach by content analysis on mapping Central Government Policies related to Poverty Alleviation in Indonesia. We found that infrastructure has a significant effect on the economy, economy mediates the effect of Infrastructure on poverty alleviation, and Government Policy does not moderate the effect of Infrastructure on poverty alleviation. Based on these findings, it is recommended that in efforts to poverty alleviation, the government should focus on making regulations that are more effective and efficient, good management and intensive collaboration across ministries/agencies, increasing the competence of human resources and the local community, as well as being in sync with improving the community's economy. The impact of (physical) infrastructure development on poverty alleviation will be more significantly if it is combined by social and economic development